Effect of Twist and Bmi1 on intraductal papillary mucinous neoplasm of the pancreas. Issue 12 (18th November 2014) - Ishikawa, Daichi; Shimada, Mitsuo; Utsunomiya, Tohru; Morine, Yuji; Imura, Satoru; Ikemoto, Tetsuya; Arakawa, Yusuke; Kanamoto, Mami; Iwahashi, Shuichi; Saito, Yu; Yamada, Shinichiro; Miyake, Hidenori
Abstract Background Intraductal papillary mucinous neoplasm (IPMN) is a well‐established entity among pancreatic neoplasms that ranges from low‐grade dysplasia to invasive carcinoma. Epithelial‐mesenchymal transition (EMT) contributes to tumor progression in various cancers. Moreover, Notch signaling is one of the important upstream effectors of EMT promotion. Currently, it is unclear whether EMT causes pathological progression of IPMN. Aim We evaluated the expression of EMT‐promoting transcription factors Twist and B cell‐specific Moloney murine leukemia virus insertion site 1 (Bmi1) in IPMN. Methods Patients who underwent resections at our institute and its affiliated hospital were enrolled in this study (n = 35). Protein expression of EMT markers Twist, Bmi1, Jagged1, and E‐cadherin in resected specimens was investigated by immunohistochemistry. Expression of these proteins was compared with the clinicopathological factors and patient survival. Results Positive expression of Twist and Bmi1 was observed in 40.0% and 42.9% of IPMNs, respectively. Twist and Bmi1 expression was significantly higher in IPMNs with high‐grade dysplasia (P < 0.05) and invasive carcinoma (P < 0.05) than that in IPMNs with low‐grade dysplasia. High expression of Twist was correlated with Jagged1 expression and inversely correlated with expression of E‐cadherin (P = 0.06 and P < 0.05, respectively). In survival analyses, the recurrence rate was significantly higher in the group that showed simultaneous high expression of Twist and Bmi1 (P < 0.05). Conclusions Expression of Twist and Bmi1 is associated with aggressiveness and poor prognoses of IPMN through EMT promotion that might be induced by Notch signaling.